Implementation of the Personnel Management Information System (SIMPEG) Policy at the Medan City Personnel and Human Resources Development Agency - Putri Mustabsirah; Maksum Syahri Lubis; Rudi Salam Sinaga (Budapest International Research and Critics University, 2021)
The aims of this study is to find out the managemet Information System (SIMPEG) Policy at the Medan City Personnel and Human Resources Development Agency. This study use qualitative research. The result of this study shows that 1. The implementation of the SIMPEG Policy in the Regional Personnel and Human Resources Development Agency in Medan City has generally been carried out well. However, it is necessary to develop the SIMPEG where it is hoped that the SIMPEG will be developed with android programming so that employees will get more service convenience. Barriers in the Personnel Management Information System (SIMPEG) at the Regional Personnel and Human Resources Development Agency of Medan City can be seen from 4 aspects, namely communication, resources, character of Implementor Institutions, and bureaucracy. The communication aspect shows that it has been carried out well as evidenced by the lack of even almost no miscommunication in the implementation of SIMPEG to employees at the Medan City BKDPSDM. The resource aspect shows that the facilities and infrastructure in BKDPSDM are quite complete, but there are shortcomings where employees often have to wait for the existing equipment to function optimally. Human resources also show that the human resources owned by the Medan City BKDSDM are also very supportive for SIMPEG to run. For the character aspect of the implementor, it seems that it is still not supportive for SIMPEG to run optimally. Both superiors and subordinates in BKDPSDM should have a good level of commitment, so that each individual can continue to do his or her job happily and without feeling pressured. The bureaucratic aspect shows that this aspect has also been carried out well and is the reason that SIMPEG is very good to be implemented.